2011
DOI: 10.1143/jjap.50.032203
|View full text |Cite
|
Sign up to set email alerts
|

Refractometric Sensor Based on a Birefringent Silica Waveguide Using a Tapered Cladding

Abstract: An integrated photonic refractometric sensor was proposed and accomplished based on a birefringent silica rib waveguide incorporating a tapered cladding, which is overlaid with a uniform high-index film. A sensing region is free of the cladding so that the modification of the birefringence incurred by an analyte could be maximized, whereas input/output sections are not subject to it. And a shadow mask was taken advantage of to produce the tapered upper cladding in the light propagation direction. The variation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2012
2012
2012
2012

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 20 publications
0
1
0
Order By: Relevance
“…It was reported that the fringe contrast depended on the ratio of the slit width to the spatial periodicity of the sensor; the regular high contrast interference pattern can be readily detected as the slit width is smaller than the spatial periodicity. Based on a brief ringent silica rib waveguide, an integrated optical refractometric sensor has been introduced recently [54]. In the reported sensor, to get rid of undesired absorptions, a uniform high index titanium dioxide (TiO 2 ) film was deposited on the whole waveguide except the sensing region located in the center.…”
Section: Fiber Optical Chemical Sensorsmentioning
confidence: 99%
“…It was reported that the fringe contrast depended on the ratio of the slit width to the spatial periodicity of the sensor; the regular high contrast interference pattern can be readily detected as the slit width is smaller than the spatial periodicity. Based on a brief ringent silica rib waveguide, an integrated optical refractometric sensor has been introduced recently [54]. In the reported sensor, to get rid of undesired absorptions, a uniform high index titanium dioxide (TiO 2 ) film was deposited on the whole waveguide except the sensing region located in the center.…”
Section: Fiber Optical Chemical Sensorsmentioning
confidence: 99%